1999
DOI: 10.1063/1.124311
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxial growth of InGaAsN:Sb/GaAs quantum wells for long-wavelength semiconductor lasers

Abstract: InGaAsN:Sb/GaAs quantum wells (QWs) were grown by solid-source molecular beam epitaxy using a N2 radio-frequency plasma source. Photoluminescence reveals an enhancement in the optical properties of InGaAsN/GaAs QWs by the introduction of Sb flux during growth. X-ray diffraction and reflection high-energy electron diffraction analyses indicate that Sb acts as a surfactant. This technique was used to improve the performance of long-wavelength InGaAsN laser diodes. A low-threshold current density of 520 A/cm2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
91
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(98 citation statements)
references
References 18 publications
4
91
1
2
Order By: Relevance
“…1 Although promising results have been obtained for Sb-free 1.5 m lasers grown by metal organic vapor phase epitaxy 2 and molecular beam epitaxy ͑MBE͒, 3,4 more rapid progress towards longer wavelength cw operation has been made with the quinary material [5][6][7][8] which benefits from the Sb surfactant effect. 1,9 In this letter we report GaInNAsSb/ GaNAs double quantum well ͑QW͒ ridge waveguide ͑RWG͒ lasers with a room-temperature cw lasing wavelength of 1.56 m. The devices were burned in for 100 h to evaluate their reliability and to ensure stability for subsequent measurements. The temperature performance was studied between 5 and 45°C in cw mode.…”
Section: Gain and Lifetime Of Gainnassb Narrow Ridge Waveguide Laser mentioning
confidence: 99%
“…1 Although promising results have been obtained for Sb-free 1.5 m lasers grown by metal organic vapor phase epitaxy 2 and molecular beam epitaxy ͑MBE͒, 3,4 more rapid progress towards longer wavelength cw operation has been made with the quinary material [5][6][7][8] which benefits from the Sb surfactant effect. 1,9 In this letter we report GaInNAsSb/ GaNAs double quantum well ͑QW͒ ridge waveguide ͑RWG͒ lasers with a room-temperature cw lasing wavelength of 1.56 m. The devices were burned in for 100 h to evaluate their reliability and to ensure stability for subsequent measurements. The temperature performance was studied between 5 and 45°C in cw mode.…”
Section: Gain and Lifetime Of Gainnassb Narrow Ridge Waveguide Laser mentioning
confidence: 99%
“…2 A few years later, Yang et al 3 demonstrated that the addition of Sb to dilute nitrides dramatically improves the material and optical quality, reduces the band gap, and modifies the band gap line-up in GaInNAs/ GaAs quantum wells ͑QWs͒. Significant progress was made in this area, [4][5][6] leading to roomtemperature continuous-wave operation at 1.55 m and recently single mode GaInNAsSb/ GaNAs QW based distributed feedback lasers at the same wavelength were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…1. Thus, atomic H can be regarded as a suitable surfactant in the MBE growth of Ga(In)NAs similar to the use of Sb reported by Yang et al [13]. Thus, we conclude that using atomic H as a surfactant and self-incorporation of H atoms for the suppression of active defects in GaNAs and GaInNAs should help to improve the overall crystal quality of these materials.…”
mentioning
confidence: 80%